The correlation between library circulation and bookstore circulation in Japan: A time series analysis / Bin Umino, Kyo Kageura and Shinichi Toda - Umino, Bin; Kageura, Kyo; Toda, Shinichi (2011)
The objective of this paper is to investigate the interrelationship between the two main book distribution channels in Japan, bookstores and libraries. For this purpose, we compare and analyse the circulation of books via bookstores and via libraries in the 60 years since the end of World War II. We also focus on domestic economic trends as an external factor influencing book circulation. Three time-series variables were analysed: total annual net paid circulation via bookstores (from 1953 to 2009), total annual circulation via public libraries (from 1958 to 2008), and the real economic growth rate, calculated on the basis of real GDP, for each calendar year (from 1956 to 2009). The circulation of books via libraries has increased almost monotonically since the 1960s, while that via bookstores has decreased since reaching a peak in 1996. Simple correlation coefficients and partial correlation coefficients were calculated to demonstrate synchronous relationships between each pair of the three time-series variables. Tests of non-correlations for each correlation coefficient were also conducted. Finally, the Granger causality test was conducted to demonstrate anterior-posterior relationships among variables. From the results of the correlation analyses and the Granger causality test, we can conclude with reasonable certainty that book circulation has been affected by economic trends, whereas the correlation between the circulation of books via bookstores and the circulation of books via libraries is in fact spurious. To eliminate the population effect, per-capita circulation was also calculated. The per-capita circulation data also supported the above conclusion.